Commercial and subsistence harvests of bowhead whales (Balaena mysticetus) in eastern Canada and West Greenland - Higdon , Jeff. W. (J. Cetacean Res. Manage., 2023)
Commercial harvesting of bowhead whales (Balaena mysticetus) from the eastern Canada-West Greenland population started with Basque whalers in the Strait of Belle Isle ca 1530 AD. Subsistence harvests have an even longer history, and the first culture to be active bowhead whalers was the Thule, which replaced the Dorset culture in the central and eastern Arctic ca 1200 AD. Previous harvest compilations have been incomplete, and back-calculated population models have thus been negatively biased. In recent decades this population has shown significant recovery and is the subject of Inuit subsistence harvests in both Canada and West Greenland. A revised historic abundance estimate is needed to examine the level of recovery; this requires inter alia a revised and updated catch series. Available information from multiple anthropological, archaeological, historic and recent sources, and estimate commercial and subsistence harvests in eastern Canada and West Greenland is summarised. From 1530–1915, commercial whalers took an estimated 55,916–67,537 (median 61,537) bowhead whales (varying assumptions on the intensity of the Basque harvest), which is known to be incomplete. Inuit harvests before commercial whaling began (1200–1529 AD) were estimated at 11,435 whales, based on the abundance of whale bone at winter houses excavated by archaeologists. After 1500 AD, Inuit whaling declined, and the total estimated harvest between 1530 AD and the end of commercial whaling was 8,406 whales. Inuit whaling declined again after commercial whalers overharvested the population and only 65 whales are known to have been harvested (or struck and lost) from 1918–2009. The Inuit harvest statistics are based on scattered data and a number of assumptions, with some evidence that at least parts of the series are underestimated. Even if harvests were higher, they would have probably not been large enough to cause population declines. The long tradition of Inuit bowhead whaling was negatively impacted by commercial harvests. Combining all harvests from 1530–2009 AD results in a total estimated kill of some 70,000 whales (not including struck and lost whales and known gaps for some nations and eras), with most (88%) taken by commercial whalers. Data quality varies considerably by nation and era, and was assigned to a 3-point scale for reliability, with over half the harvest considered to be the least reliable. This is the most comprehensive summary and estimate of bowhead harvests for this region, but is still known to be incomplete and is based on a number of assumptions and disparate data sources.